Hydrogen-Assisted Thermal Cracking for Enhanced Bio-Oil Production - Suryavansi, Ankita (Journal of Advanced Research in Petroleum Technology & Management, 2023)
This study outlines the pyrolysis and thermal cracking processes used to produce bio-oil from a variety of agricultural wastes, including used soybean frying oil, coffee grounds, and sawdust. A light fraction and a heavy fraction were created from the fractions produced during the pyrolysis and/or cracking procedures. Comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry detection (GCGC/TOFMS) was used to analyse all the fractions. While the fractions obtained by pyrolysis contained significant amounts of compounds such as furanmethanol, hexanol, and benzofuran, whose commercial value is high, the characteristics of the fractions obtained in the presence of hydrogen were similar to those of petroleum-based naphtha.